2019
DOI: 10.1590/s1677-5538.ibju.2018.0522
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation on 24-hour urine calcium in patients with calcium Urolithiasis and vitamin D deficiency

Abstract: Purpose: Hypercalciuria is one of the risk factors for calcium kidney stone formation (the most common type of urinary stones). Although vitamin D deficiency is prevalent among urolithiasis patients, the effect of vitamin D supplementation on urine calcium in these patients is still unclear. Materials and Methods: In this retrospective study, medical and laboratory tests records of 26 patients with recurrent calcium kidney stones and vitamin D deficiency treated with 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 26 publications
3
19
5
Order By: Relevance
“…Other studies failed to observe any correlations between 25(OH)D and urinary calcium excretion (19)(20)(21). The results of our previous study (24) showed that the 24-U Ca increased in vitamin D supplemented patients, which was not associated with serum 25(OH)D or PTH changes. Other results of that study suggested that the increase in 24-U Ca might be due to other factors such as dietary sodium and protein intake.…”
Section: Discussioncontrasting
confidence: 51%
“…Other studies failed to observe any correlations between 25(OH)D and urinary calcium excretion (19)(20)(21). The results of our previous study (24) showed that the 24-U Ca increased in vitamin D supplemented patients, which was not associated with serum 25(OH)D or PTH changes. Other results of that study suggested that the increase in 24-U Ca might be due to other factors such as dietary sodium and protein intake.…”
Section: Discussioncontrasting
confidence: 51%
“…Although data suggest that vitamin D supplements increase the risk of hypercalcemia by increasing intestinal calcium absorption, episodes of hypercalciuria are not correlated with hypercalcemia 31 . In a study by Tacheri et al 32 , an increase in calcium in urine from 3.74 mmoL/24 h to 5.7 mmoL/24 h was registered 32 , while in our study after the initial increase in calcium urinary values from 3.34 mmoL/24 h to 4.5 mmoL/24 h, a stagnation of its values was registered with a slight decrease by the end of monitoring. In this research, it was concluded that despite the increase in calciuria during supplementation with vitamin D, it was not correlated with the increase in vitamin D values or changes in PTH values 32 .…”
Section: Discussioncontrasting
confidence: 46%
“…There is controversy on the effect of vitamin D administration on the urolithiasis activity. Earlier reports suggested the possibility of negative impact of vitamin D supplementation on the activity of urolithiasis, and vitamin D treatment in these patients was, therefore, contraindicated [20,21].…”
Section: Discussionmentioning
confidence: 98%